2004
DOI: 10.1021/ma0305232
|View full text |Cite
|
Sign up to set email alerts
|

Parallel and Perpendicular Orientations Observed in Shear Aligned SCA Liquid Crystal of Main-Chain Polyester

Abstract: Shear alignment behavior was examined for smectic CA (SCA) phase of main-chain BB-5(3-Me) polyester using a cone-and-plate fixture. In the smectic temperature region from 100 to 140 °C, two distinct orientations have been identified by wide-angle X-ray diffraction. At temperatures lower than 130 °C, the smectic layers arrange with unit normal perpendicular to the shear direction and parallel to the velocity gradient direction (so-called parallel orientation). Shearing at high temperatures near the isotropizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 35 publications
4
68
0
Order By: Relevance
“…Here, the molecules lie perpendicular to its axis. This unusual orientation is considered to result from the preferential alignment of chain folded lamellae [11][12][13][14][15][16] under a flow of drawing or shearing. In this work, we performed dynamic mechanical measurements on fibrous BB-5(3-Me) polyester specimens with these two distinct orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the molecules lie perpendicular to its axis. This unusual orientation is considered to result from the preferential alignment of chain folded lamellae [11][12][13][14][15][16] under a flow of drawing or shearing. In this work, we performed dynamic mechanical measurements on fibrous BB-5(3-Me) polyester specimens with these two distinct orientations.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] The orientation of the macromolecular chains depends on the conditions of the test, and, in the case of drawing experiments, it has been observed that the orientation changes with temperature and strain rate. Thus, a normal, parallel orientation of the chains in relation to the stretching direction has been found for high strain rates and low temperatures, while a perpendicular orientation of the chains (anomalous orientation) is favoured at low strain rates and high temperature.…”
Section: Full Papermentioning
confidence: 99%
“…A schematic unit cell model with two chains for the K M crystalline phase of BPE-C9 (b). methylene units are all in the trans-conformation [12][13][14][15][16][17][18]. Oddnumbered BPE-Cn polyesters have two possible bends: one is from the meta-linkage (configurational bend) at the end of the mesogenic groups, and the other is from the odd-number of methylene units in the spacers (conformational bend).…”
Section: Identifications Of Crystal Structuresmentioning
confidence: 99%
“…For example, a series of BB-n polyesters (n: the number of methylene units), synthesized via the melt condensation polymerization of p,p-bibenzoic acid (A-A type) and alkylene glycols (B-B type) monomers, demonstrated the structural odd-even effect. The even-numbered BB-n polyesters exhibited a low-ordered smectic A (SmA) phase, but the mesophase of the oddnumbered ones was identified to be an anticlinically tilted smectic C (SmC A ) phase layer-by-layer [12][13][14][15][16][17][18]. As an example of the morphological odd-even effect, a series of chiral polyesters were synthesized via the solution condensation polymerization of non-racemic chiral A-B type monomers, (R This is a morphological odd-even effect: the PET(R*)-n polyesters containing the identical R* chiral center but having nZodd developed righthanded helical crystals while nZeven grew left-handed helical crystals [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%